Evaluation of chemical, thermobaric and thermochemical pre-treatment on anaerobic digestion of high-fat cattle slaughterhouse waste. (November 2017) - Harris, Peter W.; Schmidt, Thomas; McCabe, Bernadette K.
Highlights: Investigated chemical, thermobaric and thermochemical treatment of abattoir waste. Chemical and thermochemical provided greatest increases in SCOD and VFA content. Lag phase was reduced by 20% and 100% in thermochemical & thermal respectively. Study indicates thermobaric pre-treatment is most viable in an industrial context. Abstract: This work aimed to enhance the anaerobic digestion of fat-rich dissolved air flotation (DAF) sludge through chemical, thermobaric, and thermochemical pre-treatment methods. Soluble chemical oxygen demand was enhanced from 16.3% in the control to 20.84% (thermobaric), 40.82% (chemical), and 50.7% (thermochemical). Pre-treatment altered volatile fatty acid concentration by −64% (thermobaric), 127% (chemical) and 228% (thermochemical). Early inhibition was reduced by 20% in the thermochemical group, and 100% in the thermobaric group. Specific methane production was enhanced by 3.28% (chemical), 8.32% (thermobaric), and 8.49% (thermochemical) as a result of pre-treatment. Under batch digestion, thermobaric pre-treatment demonstrated the greatest improvement in methane yield with respect to degree of pre-treatment applied. Thermobaric pre-treatment was also the most viable for implementation at slaughterhouses, with potential for heat-exchange to reduce pre-treatment cost. Further investigation into long-term impact of pre-treatments in semi-continuous digestion experiments will provide additional evaluation of appropriate pre-treatment options for high-fat slaughterhouse wastewater.